Does High Pressure Induce Structural Reorganization in Linear Alcohols? A Computational Answer. Issue 19 (5th August 2016) - Mariani, Alessandro; Ballirano, Paolo; Angiolari, Federica; Caminiti, Ruggero; Gontrani, Lorenzo
Abstract: We present an exhaustive computational study on the effect of high pressure on normal alcohols with alkyl chains with lengths of three‐to‐eight carbon atoms. 1‐Propanol, 1‐butanol, 1‐pentanol, 1‐hexanol, 1‐heptanol, and 1‐octanol were studied by using classical molecular dynamics simulations and applying pressures in the range of 1 to 10 4  bar. The results of our calculations show that high‐pressure values affect the structure significantly. In particular, we have observed a marked difference in behavior for alcohols with chain lengths below six and those with more than six or seven carbon atoms, with hexanol and heptanol being boundary cases. We have named the model with the most shrunk alkyl chains as the Asclepius form inspired by the Rod of Asclepius, the universally known symbol of medicine, in which a snake is coiled around a rod. Abstract : Under pressure ! High pressures have a direct effect on the structure of n‐alcohols. Our molecular dynamics models show that above 5 kbar the characteristic micro‐heterogeneity of these compounds is replaced by a far more chaotic organization, induced by alkyl‐tail folding.